PENERAPAN ASAS KEBEBASAN BERKONTRAK DALAM PERJANJIAN SIMPAN-PINJAM YANG DILAKSANAKAN OLEH BMT SURYA MANDIRI - Rokamah, Ridho (Justicia Islamica, 2012)
PENERAPAN ASAS KEBEBASAN BERKONTRAK DALAM PERJANJIAN SIMPAN-PINJAM YANG DILAKSANAKAN OLEH BMT SURYA MANDIRIÂ Ridho RokamahAbstract: Legal relation between debtor and creditor is a part of âcivil lawâ case (hukum perdata.) It is a contract refers to a particular case. Each sides of doers can freely manage contents of contract based on âcivil legal lawâ (KUH Perdata) article 1338 which states âSemua perjanjian yang dibuat secara sah berlaku sebagai undang-undang bagi mereka yang membuatnya.â Contract content standard of BMT Surya Mandiri, substantially, suffers a financial loss for two sides.Â  Contract standard especially muz}a>rabah should be revised not only at payment system but also at âpayment durationâ and âwanprestasiâ to strengthen legal justice for both sides.This paper is to analyze this particular contract using legal jurisprudence and âcivil legal lawâ (KUH Perdata) for harmonize the two sides of doers.Â Â Â Â Â  Keywords: Perjanjian baku, asas kebebasan berkontrak, perjanjian muz}a>rabah,